2000
DOI: 10.1007/s004010051148
|View full text |Cite
|
Sign up to set email alerts
|

Axonopathy and amyotrophy in mice transgenic for human four-repeat tau protein

Abstract: Coding region and intronic mutations in the tau gene cause frontotemporal dementia and parkinsonism linked to chromosome 17. Some of these mutations lead to an overproduction of tau isoforms with four microtubule-binding repeats. Here we have expressed the longest four-repeat human brain tau isoform in transgenic mice under the control of the murine Thy1 promoter. Transgenic mice aged 3 weeks to 25 months overexpressed human tau protein in nerve cells of brain and spinal cord. Numerous abnormal, tau-immunoreac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
221
1
8

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(247 citation statements)
references
References 52 publications
17
221
1
8
Order By: Relevance
“…Thus, transgenic mice expressing human mutant P301S tau show neurodegeneration and abundant filaments made of hyperphosphorylated tau protein (15,16). By contrast, mouse lines expressing single isoforms of wildtype human tau do not produce tau filaments or develop neurodegeneration (17)(18)(19). We previously showed that the injection of brain extracts from human mutant P301S tau-expressing mice into the brains of mice transgenic for the longest human four-repeat tau isoform (ALZ17 line) induced the assembly of wild-type human tau into silver-positive inclusions and the spread of pathology from the sites of injection to neighboring brain regions (20).…”
mentioning
confidence: 99%
“…Thus, transgenic mice expressing human mutant P301S tau show neurodegeneration and abundant filaments made of hyperphosphorylated tau protein (15,16). By contrast, mouse lines expressing single isoforms of wildtype human tau do not produce tau filaments or develop neurodegeneration (17)(18)(19). We previously showed that the injection of brain extracts from human mutant P301S tau-expressing mice into the brains of mice transgenic for the longest human four-repeat tau isoform (ALZ17 line) induced the assembly of wild-type human tau into silver-positive inclusions and the spread of pathology from the sites of injection to neighboring brain regions (20).…”
mentioning
confidence: 99%
“…It was found that the hThy1 promoter gave the highest APP mRNA levels throughout the brain, most notably in hippocampus and cerebral cortex 42 . We made the same observations using all four promoters for tau expression 36 , and found subsequently that the mThy1.2 expression vector is superior to the hThy1 vector 12,19 .…”
Section: Introductionmentioning
confidence: 58%
“…For transgenic expression in neurons, a host of expression vectors is available, but in practical terms only a limited number are used. We have been mainly using the mouse Thy1.2 (mThy1.2) expression vector for expression in neurons of brain and spinal cord 14,15,[19][20][21][22] . The mThy1.2 promoter has also been successfully used to fluorescently label neurons and provide a Golgi-like vital stain 23 .…”
Section: Introductionmentioning
confidence: 99%
“…The pattern of tau splice products expressed in adult DM1 brain is similar to that normally expressed in fetal brain [22,25], which may contribute to the development of neurofibrillary tangles and hyperphosphorylated tau in DM1 [26]. It is noteworthy that forced expression of fetal tau in motor neurons of transgenic mice led to motor axonopathy and muscle wasting [27]. However, morphometric analysis of the deep peroneal nerve showed no evidence for motor axon retraction in 4 patients with DM1 [28].…”
Section: Discussionmentioning
confidence: 74%